Penyelidikan jenis mineral di Jorong Koto Baru Nagari Aie Dingin Kabupaten Solok dengan metode geolistrik Induced Polarization (IP) (Investigating the types of minerals in Jorong Koto Baru Nagari Aie Dingin Solok Regency using the geoelectric Induced Polarization (IP) method) - Hisni Rahmi; - Asrul; - Akmam (Department of Physics – Universitas Negeri Padang UNP, 2015)
Jorong Koto Baru Nagari Aie Dingin Kabupaten Solok is predict has mineral resources. The research to find deposit of several minerals have not be done. The purpose of the investigation is to identify any minerals contained in the Jorong Koto Baru based on chargeability value by Induced Polarization (IP) Geoelectrical method and distribution of minerals there. This research instrument is ARES (Automatic Resistivitymeter) to get data of apparent chargeability on the site. Data is collected and then be interpretated by Smoothness-Constraint Least Squares inversion. Data interpretation shows the actual value of chargeability and then be compared table of chargeability minerals and rocks. The result show that there are Graphite, Chalcophyrite, Copper, and Galena. Mineral Graphite (carbon compounds) are found with a thickness of 12.75 m, 43.4 m and 56.15 m. Mineral Chalchophyrite (dominated by copper element) was found with a thickness of 43.78 m and 6.15 m. Mineral Copper (copper element) was found with a thickness of 10.5 m, 15.42 m, 6.52 m and 40.1 m, while mineral Galena (lead sulfide) was found with a thickness of 2.78 m, 9.73 m, and 4.35 m. Conclusion the area has some potential mineral resources.